Modeling and application of ring stiffness condition for radial-axial ring rolling. (November 2016) - Hua, Lin; Deng, Jiadong; Qian, Dongsheng; Lan, Jian; Long, Hui
Abstract: Radial-axial ring rolling (RARR) is an advanced incremental metal-forming technology for manufacturing various seamless rings, especially for large scale rings. A primary problem for RARR is to facilitate rolling process stable and form a ring with good dimension and performance. However, RARR is an extremely complex dynamic rolling process with high flexibility. To reasonably control guide roll is an important approach to keep rolling process stable during RARR. In this paper, a mathematical model of ring stiffness condition for RARR was established based on the force method. Then the influence factors to ring stiffness were discussed, especially the section bending moment factor. To verify the ring stiffness model, finite element (FE) simulation was adopted. In addition, a comparison of different ring stiffness models was made. It can be found the proposed stiffness model has a high accuracy. Furthermore, a control method of the pressure in the hydraulic cylinder to adjust the guiding force based on the stiffness model was proposed. By FE simulation of RARR, an appropriate adjustment coefficient to determine the guiding force was obtained. Finally, an experiment of RARR for a large ring was carried out. The rolling process was very smooth and steady, and a super-large ring with diameter more than 9 m was manufactured successfully. Highlights: A mathematical model of ring stiffness condition for RARR is established. The influence factors to ring stiffness are discussed in detail. The proposed stiffness model has a high accuracy. A control method of guiding force based on the stiffness model is proposed.